MISSION, PHILOSOPHY AND GOALS AS THE BASIS OF MECHANISMS OF PUBLIC ADMINISTRATION OF LOCAL TAXES (ON THE EXAMPLE OF UKRAINE AND STATE OF NEVADA) - Кур`ян, Вікторія Валеріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: to investigate and carry out a comparative analysis of the mission, philosophy and objectives of the mechanisms of public administration of local taxes (on the example of Ukraine and Nevada, USA). The research methodology is based on the historical method, methods of comparison, analysis and synthesis, as well as the principle of determinism. Results: it is established that the difference in the purposes of public administration of local taxes in Ukraine and the United States is significant. Mission and philosophy as the basis of mechanisms of public administration of local taxes are absent in Ukraine. It was found that since the mechanism of public administration of local taxes we understand a certain formula of interaction of elements of the local tax system in accordance with general scientific principles of taxation and principles of system management, which aims to achieve social welfare by performing social tasks provided by social (material, labor), scientific) resources, the action of mechanisms of public administration of local taxes should ensure the balance not only of the financial system of a particular territorial unit but also the financial system of the state, and therefore, in our opinion, certain types of mechanisms should be so to speak completed programs, algorithms will function, work independently without the need for constant strict control by the state. Mission and philosophy as the basis of mechanisms of public administration of local taxes should be aimed at public understanding of the local tax system as work for the public good of the territorial unit, as well as work aimed at the absolute public good of the country as a whole. Discussion: given the practice of public administration of local taxes in progressive countries, in particular, the United States, it is proposed to improve the mechanisms of public administration of local taxes in Ukraine based on mission, philosophy and goals, and it is recommended to introduce detailed regulation of tax collection mechanisms at the local level.